The contradiction of international trends in freedom of association. (3rd July 2021) - Peetz, David
ABSTRACT: There is a contradiction in international patterns: freedom of association seems, if anything, to have been enhanced, yet union rights appear to have been under increasing threat. The existence of full freedom of association rights is normal in developed countries. The imposition of major restrictions on freedom of association is typically associated with military coups, juntas, martial law or dictatorships. As countries become more economically developed and more democratic, rights to freedom of association are generally enhanced if they are not already ubiquitous. Yet union rights and union density are in decline. This pattern seems to be part of the contradiction of the move to greater marketisation, relating to a separation of industrial relations issues from human rights.